Faith in a new Scotland: dissent, piety, and political culture, 1760-1820 - Smith, PM (2024)

(untitled)
Among the profound social and economic changes which shaped Scotland from the mid-eighteenth and into the early nineteenth centuries, the rapid growth of religious dissent altered Scotland’s religious complexion. Dissenting Presbyterianism acted as a force which preserved traditional forms of popular piety and as a source of spiritual vitality within Scottish society. The denominations comprising Presbyterian dissent attracted broad support from the middling and lower orders—around one third of Lowland Scots by 1800—who sought a more orthodox and gospel-centric religious expression than what they found within the Kirk. Dissenting Presbyterianism’s shared values and ideals led its adherents to voice a largely coherent critique of not only the spiritual condition of Scottish society but elements of the civil status quo as well. In doing so, dissenting Presbyterians created not only competing visions of the Scottish Church, but also offered alternate conceptions of Britishness and how Scots related to the civil state.